2019
DOI: 10.2147/cmar.s204357
|View full text |Cite
|
Sign up to set email alerts
|

<p>HMGB3 silence inhibits breast cancer cell proliferation and tumor growth by interacting with hypoxia-inducible factor 1α</p>

Abstract: Background: Breast cancer is the most common malignant tumor that affects women with higher incidence. High-mobility group box 3 (HMGB3) plays critical functions in DNA repair, recombination, transcription and replication. This study aimed to investigate the effects of HMGB3 silence on mammosphere formation and tumor growth of breast cancer. Methods: LV5-HMGB3 and LV3-siHMGB3 vectors were transfected into MCF10A, MDA-MB-231, HCC1937, ZR-75-1 and MCF7 cells. Cell counting kit-8 (CCK-8) assay was used to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 41 publications
2
45
0
Order By: Relevance
“…We also found that HMGB3 was over-expressed in GC and negatively correlated with miR-145-5p. Consistent with our results, it has been reported that HMGB3 is highly expressed in breast cancer, colorectal cancer and glioblastoma, and can regulate the development of tumors [35][36][37]. To verify the relationship between circBVES and HMGB3, we found that low expression of circBVES inhibited HMGB3 expression at mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 91%
“…We also found that HMGB3 was over-expressed in GC and negatively correlated with miR-145-5p. Consistent with our results, it has been reported that HMGB3 is highly expressed in breast cancer, colorectal cancer and glioblastoma, and can regulate the development of tumors [35][36][37]. To verify the relationship between circBVES and HMGB3, we found that low expression of circBVES inhibited HMGB3 expression at mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 91%
“…156 Later research revealed that this mediation could be strengthened by HMGB3. 157 Clinical significance of HMGB family members in human cancers HMGB family members are widely involved in carcinogenesis, increasing evidence also indicate that HMGB family members are promising targets for cancer treatment. Moreover, the diagnostic and prognostic roles of HMGB family members are gradually revealed.…”
Section: Hmgb3mentioning
confidence: 99%
“…Research by Zhang et al proved that overexpressed HMGB3 promoted proliferation and migration of cancer cells, accelerating the progression of colorectal cancer [ 25 ]. Studies by Gu et al demonstrated that silencing HMGB3 expression suppressed breast cancer cell proliferation, thus inhibited tumor growth [ 26 ]. It has been proved that the regulation of HMGB3 by tumor suppressive miR-205-5p suppressed cancer cell aggressiveness and participated in prostate cancer progression [ 27 ].…”
Section: Discussionmentioning
confidence: 99%